miR-16-1 Promotes the Aberrant α-Synuclein Accumulation in Parkinson Disease via Targeting Heat Shock Protein 70 - Zhelin Zhang; Yan Cheng (The Scientific World Journal)
There is striking evidence that heat shock protein 70 (Hsp70) negatively regulates α-synuclein aggregation, which plays a significant role in the formation and progression of Parkinson disease (PD). However, how the Hsp70 in neurons fails to prevent or even reverse α-synuclein aggregation and toxicity in PD still remains to be determined. In the present study, we constructed an α-synuclein-overexpressed human neuroblastoma cell line, SH-SY5Y-Syn, in which the blockage of Hsp70 promoted α-synuclein aggregation. And we also found that miR-16-1 downregulated Hsp70 and promoted α-synuclein aggregation in the SH-SY5Y-Syn cells. This study revealed a novel regulatory mechanism of Hsp70 expression, which might contribute to the PD development.